The Effect of Infection Prevention and Control Online Training Compared to Face-to-face Training on Knowledge, Attitude and Practice - Prihanti, Gita Sekar; Wilyani, Dwi; Seta, Anang Bayu; Wismananda, Ari Viandri; Rahmawati, Mega; Adzani, Nicky Novita; Miskiyah, Zakiyatul; Kurnia, Anggraini Dwi; Nugroho, Muhammad Adin (Universitas Aisyah Pringsewu, 2024)
Research on Infection Prevention and Control (IPC) is often conducted at hospitals rather than Public Health Center (PHC) whereas it role as a first response facility for the community has an inherent contribution to prevention efforts at the family level, becoming the research gap requiring special attention to this issue. The difference to other previous research is that this study was conducted online, while the previous one in Pesantren II PHC, Kediri, used IPC face-to-face training. Predicting the potential for a more practical and efficient IPC method, this study aimed to determine the effect of IPC online compared to IPC face-to-face training on knowledge, attitudes, and practice. This study was a quasi-experiment with two group pretest-posttest designs. The sample was 102 people, using Total Sampling Techniques divided into IPC online training and IPC face-to-face training groups. Knowledge and attitude were assessed using questionnaires developed by reviewing relevant literature and adapting the content from related studies, while practice was assessed using observation sheets. The data were analyzed with the McNemar test that showed the effects of knowledge, attitude, and practices not only in IPC face-to-face training (P=0,000; 0,002; and 0,000) but also in online training (P=0,008; 0,016; and 0,000), and affect COVID-19 knowledge (P=0,000), but it does not affect the COVID-19 attitude (P=1,000). The results showed an increase in knowledge, attitudes and practice respondents after IPC online training and has the same effectiveness as IPC face-to-face training.